THE USE OF PARTNERSHIP IN PURCHASING - ELENA SIMA; GEORGE BĂLAN (Annals of the University of Petrosani: Economics, 2014)
The partnership is now increasingly used in all areas thanks to the synergy it implies and of the benefits demonstrated. And in today's economy benefits of the partnership are widely recognized. Partnership in purchase makes no exception. This paper presents the benefits of a partnership-based purchases compared to those of traditional purchasing. Less well known is that a partnership built and/or implemented incorrectly and may result in additional costs and thus lead to disadvantages for both companies. For this reason, the paper aims to present what a partnership is, to show which steps should be taken to build a successful partnership and to exemplify through companies which have implemented correctly this type of collaboration, obtaining exceptional results.